DOP65 Development and validation of the TUMMY-UC, a patient-reported outcome in pediatric Ulcerative Colitis: A multicenter prospective study. (21st January 2022) - Turner, D; Marcovitch, L; Focht, G; Carmon, N; Tersigni, C; Ledder, O; Lev Tzion, R; Frost, K; Church, P C; Baldassano, R; Otley, A; Kappelman, M; et al.
Abstract: Background: In developing a patient-reported outcome (PRO) for pediatric ulcerative colitis (UC) with guidance from FDA and EMA, 8 items were previously selected based on 79 concept elicitation interviews. An observer RO (ObsRO) was determined to be required for children younger than 8 years. Here, we aimed to finalize the included items and to validate the TUMMY-UC for its psychometric properties. Methods: The structure and exact wording of the PRO and the ObsRO versions were determined by cognitive debriefing interviews with children and their caregivers. Weights were assigned to each item based on ranking of importance. Then, in a prospective multicenter study, children with UC between 2–18 years who either underwent colonoscopy or provided stool for calprotectin completed the TUMMY-UC during 4 consecutive days, as well as 7 and 21 days thereafter for evaluating reliability and responsiveness. Construct and discriminative validity were assessed by different measures of disease severity and quality of life (QOL). Results: In an iterative process of 129 cognitive interviews, the exact wording of the TUMMY-UC was determined. The PRO and ObsRO were formatted with identical structure to ensure conceptual equivalence for incorporating into one score. 71 children were included in the validation study (39 with colonoscopy and 32 with calprotectin; age 12.3±4.1 years, 26 (36%) in remission, 20 (29%) with moderate-severe disease). There was excellent reliability in the repeated day assessments (ICC 0.93 (0.88–0.96); p<0.001) and after 1 week in those judged as unchanged (0.90 (0.81–0.95); p<0.001). The TUMMY-UC total score had moderate to strong correlations with all constructs of disease severity: r=0.64 with UC Endoscopic Index of Severity (UCEIS, Figure 1 ), r=0.66 with IMPACT QOL questionnaire, r=0.43 with calprotectin, r=0.82 with the PUCAI, r=0.76 with patient/caregiver global assessment, r=0.5 with CRP, and r=-0.36 with albumin (all p<0.015). There was a slight superiority to combining TUMMY-UC scores of two consecutive days. The index had excellent discrimination of disease activity categories (figure 2) with a score<9 defining remission (Sen=93%, Spec=84%, AUROC=0.95 (95%CI 0.89–0.99). Showing high responsiveness, the DTUMMY-UC differentiated well between children who improved, worsened or remained unchanged after 3 weeks (Figure 3) . The best cutoff of the TUMMY-UC to define response was a change of ≥10 points (AUROC 0.93 (95%CI 0.86–0.99)). Conclusion: The TUMMY-UC, constructed from a PRO and ObsRO versions for children 8–18 and 2–7 years, respectively, is a reliable, valid and responsive index which can be now used in clinical practice and as an outcome measure in clinical trials.